Health professionals' perspectives of integrating meditation into cardiovascular care: A descriptive qualitative study. (25th May 2022) - Rao, Angela; DiGiacomo, Michelle; Phillips, Jane L.; Hickman, Louise D.
Abstract: Preliminary research suggests that meditation may provide benefits in psychological health and well‐being in people with cardiovascular disease (CVD). However, little is known about health professionals' perceptions of the barriers and facilitators to integrating meditation into CVD. A descriptive qualitative study design with semi‐structured interviews was used to explore the acceptability of integrating meditation into outpatient CVD programs and the organisational factors that may affect its integration. Clinicians were recruited through purposive and snowball sampling. E‐mail addresses were obtained from publicly listed profiles of cardiovascular and relevant health organisations. Interview questions included perspectives of organising or delivering meditation within a health setting, format of meditation delivery, organisational or other factors that facilitate or present barriers to integrating meditation into clinical practice, and perceived risks associated with integrating meditation in clinical settings. Verbatim transcripts were thematically analysed using an inductive approach and the Braun and Clarke (2006) method to identify themes within barriers and facilitators to implementation. Eighteen predominately female (61%) senior nursing and medical professionals (61%), as well as health managers (17%), psychologists (11%) and allied health professionals (11%), aged 40–60 years were interviewed between 18 May 2017 and 29 March 2018 in Australia via telephone, or face‐to‐face at a university or the participants' workplace. Three key themes were identified including: enhancing awareness of meditation within a biomedical model of care, building the evidence for meditation in CVD and finding an organisational fit for meditation in cardiovascular care. Meditation was perceived to sit outside the existing health service structure, which prioritised the delivery of medical care. Health professionals perceived that some physicians did not recognise the potential for meditation to improve cardiovascular outcomes while others acknowledged meditation's positive benefits as a safe, low‐cost strategy. The benefits of meditation were perceived as subjective, based on preliminary evidence. Health professionals perceived that aligning meditation with health organisational objectives and integrating meditation into outpatient cardiac rehabilitation and community‐based secondary prevention pathways is needed. A fully powered clinical trial is required to strengthen the evidence regarding the role of meditation for psychological health in CVD. Generating clinician engagement and support is necessary to enhance awareness of meditation's use in cardiovascular secondary prevention.